Synthesis, Characterization and Antimicrobial Activities of Chalcones and Their Post Transformation to Pyrazole Derivatives - Ramyashree, D.; Raghavendra, K.R.; Kumar, A. Dileep; Vagish, C.B.; Kumar, K. Ajay (Asian Journal of Chemistry, 2017)
An efficient procedure for the synthesis of trisubstituted pyrazoles was developed. Claisen-Schmidt condensation of 2,4,5-trimethoxybenzaldehyde and substituted acetophenone in the presence of aqueous alkaline bases produced chalcones. The cyclocondensation reaction of chalcones and phenyl hydrazine hydrochloride catalyzed by an acid produced trisubstituted pyrazolines in good yields. The synthesized new compounds were characterized by spectral studies and elemental analysis and some of the intermediate chalcones by single crystal X-ray diffraction studies. The compounds were screened in vitro for their antimicrobial susceptibilities against different bacteria and fungi species.